Data Communications and Networks - Miller Dave (MC Graw Hill, 2005)
A friendlier voice in an area crowded with technical, formal textbooks, Miller’s style reaches the students quickly and effectively. The abundance of chapter projects and the audio/visual support of concepts enables instructors to keep students engaged.